Analysis of the Authority of the Constitutional Court in Reviewing Laws - Putri Octaviani (JUSTICES: Journal of Law, 2024)
The authority of the Constitutional Court is a separate study in this article. The authority of the Constitutional Court in accordance with the provisions of Article 24C Paragraphs (1) and (2) is to adjudicate at the first and final level to test laws against the Constitution, decide disputes over the authority of state institutions whose authority is granted by the Constitution, decide on the dissolution of political parties and decide disputes regarding the results of general elections. . Apart from that, the Constitutional Court can also give decisions to the DPR if they commit violations and also the President and Vice President who are submitted to the Constitutional Court